Building a Durable Response to HIV/AIDS: Implications for Health Systems - Atun, Rifat; Bataringaya, Jacqueline (Atun, R., & Bataringaya, J. (2011). Building a durable response to HIV/AIDS: implications for health systems. JAIDS Journal of Acquired Immune Deficiency Syndromes, 57, S91-S95., 2011)
The remarkable rise in investments for HIV control programs in 2003-2010 enabled an unprecedented expansion of access to HIV services in low-income and middle-income countries. By the end of 2010, more than 5.2 million people were receiving antiretroviral therapy (ART), which transformed HIV infection, once a death sentence, into a long-term illness. The rapid expansion in the number of persons receiving ART means that health systems must continue to provide acute life-saving care for those with advanced HIV/AIDS although also providing chronic care services to expanding cohorts of more stable patients who are doing well on ART. This expansion also means a transition from an emergency response to the epidemic, characterized by a public health approach, to a more integrated and durable approach to HIV prevention, care, and treatment services that fosters individualized care for those requiring long-term antiretroviral treatment. Yet most low-income and middle-income countries, which have weak health systems, are poorly prepared to make this transition. In this article, we highlight the challenges health systems face in developing a sustained and durable response to HIV/AIDS. The article analyses the readiness of health systems to combine rapid expansion of ART access with long-term treatment and continuity of care for a growing cohort of patients. We argue that effective management of a transition from an emergency AIDS response to long-term programatic strategies will require a paradigm shift that enables leveraging investments in HIV to build sustainable health systems for managing large cohorts of patients receiving ART although meeting the immediate needs of those who remain without access to HIV treatment and care.
Keywords: AIDS; Sustainability; Chronic illness; HIV; Health systems